Cloud-network coordination service and application for telecom operators - Tian CHEN; Yongbing FAN; Nan CHEN; Yangchun LI; Linze WU (Dianxin kexue)
Coordination and innovation of cloud-network will become the differentiated competitive advantage of telecom operators,the integration innovation based on the existing cloud network soltions will be the basic,and the business innovation of cloud-network coordination will be the most important.Based on this,the core concept,industry development,typical services,and industry trends were reviewed and analyzed.The core needs of business application of cloud-network coordination of telecom operators were summarized.A hierarchical functional architecture of cloud-network coordination service based on overlay technology was analyzed,and the key technologies were described.The reference system architecture of cloud-network coordination of telecom operators were proposed based on the cloud business needs and network developing status of telecom operators.And the typical business scenaries of cloud-network coordination of telecom operators were emphatically analyzed.